In-Fiber Gratings for Simultaneous Monitoring Temperature and Strain in Ultrahigh Temperature - Yang, H.Z.; Qiao, X.G.; Wang, Y.P.; Ali, M.M.; Lai, M.H.; Lim, Kok Sing; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2015)
In this letter, a pair of regenerated gratings with Bragg wavelengths of 1547 and 1304 nm in a single piece of single-mode fiber has been fabricated for simultaneous monitoring of temperature and strain in ultrahigh temperature environment. A 3× 3 matrix is used to characterize the cross sensitivity of the proposed sensor in which the strain sensitivity varies with temperature change. The proposed structure exhibits the deviation of 28.3 μ ε and 4.1 °C at the ranges of 0-1000 μ ε and 25 °C-900 °C, respectively.